Pregnancy and perinatal outcomes in women with polycystic ovarian syndrome - Rizwana, A.; Rajkumar, Shery Angel; Anuradha, C. R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To study the pregnancy and perinatal outcomes in women with PCOS with normal women and to study the incidence of complications like menstrual irregularities, mode of conception, gestational diabetes mellitus, pre eclampsia, preterm labour and NICU admissions in women with PCOS. Methods: It was prospective comparatives study done in 100 women to compare outcome in pregnancy with PCOS and normal women. A detailed history, general and obstetric examination, antenatal investigations, routine dating scan, glucose challenge test at 24 to 28 weeks in study and control groups, blood pressure recording and urine for proteinuria after 20 weeks to evaluate preeclampsia. After delivery, birth weight and APGAR score at 1 and 5 minutes were recorded. Body mass index was calculated and pregnancy outcome studied and compared. Results: Out of 50 women with PCOS 13 developed GDM, 10 developed pre eclampsia, 6 had abortion, 4 went into preterm labour. 15 babies required NICU admission. Conclusions: Pregnancy complications like GDM, pre eclampsia, preterm labour, abortions and neonatal complications like NICU admissions are higher in women with PCOS when compared with normal women. Hence PCOS needs to be diagnosed early and treated accordingly to prevent pregnancy complications.